Coronary anomalies and anatomical variants detected by coronary computed tomographic angiography in Kashmir, India - Rafiq, Suhail; Mohiuddin, Irshad; Nazir, Imran; Faizan, Malik (International Journal of Research in Medical Sciences, 2020)
Background: Coronary Artery Anomalies (CAAs) presenting in adulthood are rare and associated with adverse cardiac events, including sudden cardiac death. Coronary artery anomaly is the second most common cause of Sudden Cardiac Death (SCD) in young athletes. Cardiac Computed Tomographic Angiography (CTA) is a readily available non-invasive imaging modality that provides high-resolution anatomical information of the coronary arteries. Multi-detector row CT is superior to conventional angiography in deﬁning the ostial origin and proximal path of anomalous coronary branches. Methods: This was a prospective study included 186 patients who underwent coronary CTA from December 2018 to November 2019 in Government medical College, Srinagar on a 256 slice CT. The indications for coronary CTA were an equivocal, or non-diagnostic stress test, atypical chest pain, suspected anomalous coronary, as well as the evaluation of cardiac cause of syncope. Results: Ramus intermedius was the most common anatomical variant seen in 25 patients (13.4%). The prevalence of coronary anomalies in this study was 5.66% including myocarding bridging. The most common anomaly was high take off of coronary artery from sinotubular junction accounting for 1.6%. Conclusions: Coronary Computed Tomographic angiography is much superior in detecting coronary artery anomalies than invasive coronary angiography because of the absence of soft tissue information like as is needed in myocardial bridging. Proper knowledge of the anomalies and their clinical significance is highly important in planning treatment and easing hardships of cardiologists in dealing with them.